Demographic Factors Impacting the Financial Risk Tolerance of Retail Investors of Urban West Bengal - Bhattacharya, Amrita; Dutta, Avijan (Indian Journal of Finance, 2019)
Prior knowledge of willingness or capacity to take financial risks of a retail investor can be very useful in targeting potential clients for investment agencies offering various low, medium, or high risk instruments for investment. Previous research has showed that the financial risk tolerance (FRT) of an individual is influenced by several demographic factors of the individual such as age, gender, marital status, education, profession, income, number of dependents in the family, etc. The capacity also varies from country to country and place to place within a country. Hence, knowledge of the demographic data of the individual can help researchers to understand how each of these factors impact the retail investors residing in a particular place, city, or a state in taking financial risk. In this paper, we collected primary demographic data from 2000 residents of Kolkata, Asansol, and Durgapur, the three major cities of the state of West Bengal in India with an aim to find out the impact of each of these demographic factors of the respondents (the potential retail investors) on their tolerance to financial risk. The primary data were analyzed using logistic regression method which revealed gender and profession as the two demographic factors that had the most significant impact on the FRT of the retail investors; whereas, income and number of dependents had a negligible impact.